Aging Changes Effective Connectivity of Motor Networks During Motor Execution and Motor Imagery - Wang, Li; Zhang, Ye; Zhang, Jingna; Sang, Linqiong; Li, Pengyue; Yan, Rubing; Qiu, Mingguo; Liu, Chen (Frontiers in Aging Neuroscience, 2019)
Age-related neurodegenerative and neurochemical changes are thought to underlie a decline in motor function, but the changes in the effective connectivity within the motor network that come with aging are not clear. Our objective was to investigate the age-related changes in the dynamic interaction between cortical motor regions. Twenty young subjects and 20 older subjects underwent two functional magnetic resonance imaging (fMRI) experiments, right hand motor execution (ME) and right hand motor imagery (MI). Conditional Granger causality analysis was used to compare young and older adults’ effective connectivity among regions of the motor network during the tasks. The more effective connections among motor regions in older adults were found during ME; however, the effective connections within-domain hemisphere were reduced, and the blood oxygenation level dependent (BOLD) signal was significantly delayed in older adults during MI. Supplementary motor area (SMA) had a significantly higher In+Out degree within the network during ME and MI in older adults. Our results revealed a dynamic interaction within the motor network altered with aging during ME and MI, which suggested that the interaction with cortical motor neurons caused by the mental task was more difficult with aging. The age-related effects on the motor cortical network provide a new insight into our understanding of neurodegeneration in older individuals.